2015
DOI: 10.1007/s00213-015-4174-9
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation in rats of impairments of memory by scopolamine, a muscarinic receptor antagonist, by mecamylamine, a nicotinic receptor antagonist

Abstract: Rationale Scopolamine, a muscarinic antagonist, impairs learning and memory for many tasks, supporting an important role for the cholinergic system in these cognitive functions. The findings are most often interpreted to indicate that a decrease in postsynaptic muscarinic receptor activation mediates the memory impairments. However, scopolamine also results in increased release of acetylcholine in the brain as a result of blocking presynaptic muscarinic receptors. Objectives The present experiments assess wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…The lack of selectivity of pharmacological compounds makes the interpretation of mechanism of action unclear. Newman and Gold () showed that the cholinergic tone that is too low or too high is related to poor cognitive functions, depending on the task. In their study, scopolamine alters memory processes by acting on postsynaptic mAChRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of selectivity of pharmacological compounds makes the interpretation of mechanism of action unclear. Newman and Gold () showed that the cholinergic tone that is too low or too high is related to poor cognitive functions, depending on the task. In their study, scopolamine alters memory processes by acting on postsynaptic mAChRs.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, scopolamine alters memory processes by acting on postsynaptic mAChRs. But it also acts on presynaptic M2 mAChRs, thus increasing the release of ACh, and accordingly improves memory processes (Newman & Gold, ). In the present study, the lack of effect of telenzepine in reversing spatial memory impairment (in comparison with social memory recognition) could result from these puzzling effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, we submit that this role is likely supported by a wider network of distributed mechanisms (Sarter et al, 2005; Egorov et al, 2006; Esclassan et al, 2009; Hasselmo and Sarter, 2011; Baysinger et al, 2012), including cholinergic projections to perirhinal cortex (Bang and Brown, 2009) and the septohippocampal system (Givens and Olton, 1995; Seeger at al., 2004; Raybuck and Gould, 2010; Newman and Gold, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of the “SCO challenge” model is, that it could also result in an increased release of acetylcholine in the brain by blocking presynaptic muscarinic receptors. This, through the excessive activation of nicotinic receptors, may also mediate the negative effects of SCO on memory [27].…”
Section: Discussionmentioning
confidence: 99%